2013
DOI: 10.1007/s10722-013-0019-8
|View full text |Cite
|
Sign up to set email alerts
|

Domestication and association analysis of Hd1 in Chinese mini-core collections of rice

Abstract: Hd1 is one of the major photoperiod genes with high degree of polymorphisms and contributes to rice (Oryza sativa L.) flowering in different light conditions. Ninety-two rice landraces and 111 accessions of common wild rice (O. rufipogon Griff.) from the mini-core collections in China were selected and sequenced to analyze the domestication process and association of Hd1 with rice flowering. Association analysis revealed that three insertions and two deletions in the coding region of Hd1 are highly correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…The sequences of Hd1 , DTH8 , Ghd7 and OsPRR37 (Table S3) were collected from five studies reported by Wei et al (), Fujino et al (), Wei et al (), Lu et al () and Koo et al (). To ensure the samples covering all distribution areas and rice subgroups, we further sequenced 5, 8, 7 and 14 accessions for Hd1 , DTH8 , Ghd7 and OsPRR37, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The sequences of Hd1 , DTH8 , Ghd7 and OsPRR37 (Table S3) were collected from five studies reported by Wei et al (), Fujino et al (), Wei et al (), Lu et al () and Koo et al (). To ensure the samples covering all distribution areas and rice subgroups, we further sequenced 5, 8, 7 and 14 accessions for Hd1 , DTH8 , Ghd7 and OsPRR37, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…All accessions were sequenced by ABI3730XL automatic sequencer (Applied Biosystems). Since heterozygous individuals may exist for a small number of cultivars (Wei et al ), PCR fragments of heterozygous samples were cloned into EASY vectors (Transgen, China) and three cloned DNA fragments were sequenced for each individual. Taq errors occur randomly so polymorphisms shared by more than two clones are unlikely to be artificial (Eyre et al ; Zheng and Ge ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The non-synonymous mutations that occur in the CDS will lead to creating diversity at the protein level (Lu et al, 2012). Based on these non-synonymous mutations it is possible to identify functional protein-types owing to the fact that mutations at functional domains could lead to a conformational change of the protein resulting altered functionality (Lu et al, 2012;Wei et al, 2014;Li et al, 2015). In the current study, based on 14 such sites with nonsynonymous mutations (10 SNPs and 4 InDel sites) within the CDS, nine protein-types XA21-1 to XA21-9) were identified ( Figure 2).…”
Section: Thirteen Confirmed Xa21 Haplotypes and Nine Protein-typesmentioning
confidence: 99%